2002
DOI: 10.1023/a:1019819925257
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Data obtained in studies of the nature of the correlation which we have previously observed [10,17] between mitochondrial depolarization and the level of disruption of Ca2+ homeostasis in cultivated brain neuronsare summarized. Experiments were performed on cultured cerebellar granule cells loaded with Fura-2-AM or rhodamine 123 to measure changes in cytoplasmic Ca2+ and mitochondrial potential during pathogenic treatments of the cells. Prolonged exposure to 100 microM glutamate induced a reversible increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 13 publications
6
19
0
Order By: Relevance
“…The procedure of isolation of cell suspension for neuron culturing was described elsewhere [3,5,6]. The cells in culture were washed with a control solution containing (in mM): 130 NaCl, 5.6 KCl, 1.8 CaCl 2 , 1.0 MgCl 2 , 20 HEPES, 5.0 glucose, pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure of isolation of cell suspension for neuron culturing was described elsewhere [3,5,6]. The cells in culture were washed with a control solution containing (in mM): 130 NaCl, 5.6 KCl, 1.8 CaCl 2 , 1.0 MgCl 2 , 20 HEPES, 5.0 glucose, pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…Address for corre spondence: sorokina@nczd.ru. E. G. SorokinaThe decrease in ATP content in neurons during brain hypoxia and hyperstimulation of glutamate receptors can disturb intracellular and intercellular signaling in cerebral neurons, in particular, ionic homeostasis, activity of glycolytic and oxidative phosphorylation enzymes, mitochondrial Ca 2+ uptake, and protein synthesis [6][7][8]10,11,13]. Previous studies showed that ATP content in cultured cerebellar granule cells (CGC) decreased immediately after application of glutamate (Glu) [1,2,8,3].…”
mentioning
confidence: 99%
“…Cell suspension for culturing was obtained as described elsewhere [3]. This suspension was put on cover glasses (1 hippocampus, 200 ml per 1 glass) coated with poly-D-lysine (10 mg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Selective peptide agonist of proteinase-activated type 1 receptors simulated, but receptor antagonist suppressed the neuroprotective effect of thrombin. Our results suggest that peptide antagonist of type 1 receptors play a role in the mechanisms of neuronal protection from glutamate toxicity.Hyperstimulation of glutamate receptors underlies death of brain neurons during ischemic and hemorrhagic strokes, brain traumas, and some neurodegenerative diseases [3,4,7]. These disorders are associated with increased permeability of the blood-brain barrier, which results in the appearance of serine thrombin proteinase in the nervous tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation